THE INFLUENCE OF PRODUCTION COST ON THE PERFORMANCE OF DAIRY CATTLE IN THE REGION - Гордієвич, О. А. (Scientific Progress & Innovations, 2018)
Grouping of agricultural enterprises of Rivne region, depending on the cost per one cow was conducted in the article. The studies mathematical models of correlation between the level of costs and related performance indicators using their graphic images. In the result of studies mathematical models of correlation between the level of costs and the relevant output indicators using their graphic images were built. By the analysis of mathematical models amount of expenditures, causing a high performance, low cost and best possible level of cost recovery on a cow in agricultural enterprises in the region were established.